Strategic Planning of Livestock: A Commercial Soft Technology Based on the Supply Chain Strategy in Golestan Provinance - Ali NaghiMosleh Shirazi; Mohammad Nazari (International Journal of Supply Chain Management, 2019)
The aim of this study is strategic planning of poultry cluster to determine the leverage points based on the supply chain strategy and to offer approaches according to commercial soft technology maturity. The study was performed using field study and documentation between September 2017 and August 2018.  The results highlight the leverage points regarding supply and demand management of chicken meat with an emphasis on export market and low maturity of business technology in Golestan poultry markets. Some solutions are presented with regard to the current situation of the markets which are basically based on business soft technology.